The effect of core stabilization exercises and shock wave therapy in patients with radiculopathy - J. Bubelis (Neurologijos seminarai)
Background. Radiculopathy is a damage to the nerve root of the lumbar spine, which develops due to nerve root pressure and irritation. Lumbar radiculopathy is characterized by a wide variety of symptoms including the most common: lower back pain and lower limb pain, muscle weakness, disorders of proprioreceptive and postural control, which adversely affect the daily activities and quality of life of a person and result in a decrease in labour productivity in the working age population as well as disability development. Physical exercises and physiotherapy used during physical therapy have shown to reduce pain, improve and manage balance. Materials and methods. The study involved 40 subjects (22 women and 18 men) diagnosed with lumbar radiculopathy. The subjects were randomly divided into two groups of 20 subjects in each group; Group I had a cycle of spinal stabilization exercises, and Group II had a cycle of spinal stabilization exercises and shock wave therapy sessions. Visual Analogue Scale (VAS) was selected for pain assessment; for the dynamic stability assessment, the modified Star Excursion Balance Test was selected; and for the evaluation of trunk muscle static strength endurance two tests were chosen: abdominal muscle static strength endurance test and back muscle static strength endurance test. The data were processed by mathematical statistical analysis. Results. The severity of pain after the use of different physiotherapy programs decreased in both groups. In Group I, the pain decreased from 5.77±1.88 points to 3.85±1.25 points (the change in pain intensity was 1.92±0.19 points); in Group II, the pain decreased from 5.40±1.24 points to 2.55±1.05 points (pain intensity change – 2.85±0.63 points). By assessing the changes in dynamic stability of subjects after 4 weeks, the physiotherapy sessions showed an improvement in the dynamics of stability in both groups, but greater changes were recorded in Group II subjects with a cycle of spinal stabilization and shock wave therapy. Also, before and after the cycle of physiotherapy, the coefficient of the combined result was calculated which indicated whether there was a possibility of injury due to deterioration of dynamism stability and its management. Before the cycle of physiotherapy, the combined result in Group I was 92.3% and in Group II it was 92.9%. After 4 weeks of applied physiotherapy, the combined result coefficient increased in both groups: on Group I it increased by 2.8% and in Group II by 3.5%. After the cycle of physiotherapy, the combined result in Group I was 95.1%, while in the Group II it was 96.4%. It is estimated that if the combined result is less than 94%, there is an in creased probability of traumas. Thus, before the cycle of physiotherapy, individuals with radiculopathy and experiencing moderate pain are more likely to experience lower limb traumas due to dynamic changes in stability. After the cycle of exercises, we see that the combined result has reached more than 94% and it indicates that the probability of suffering injuries has decreased (p=0.032). Also, after physiotherapy, an improvement in abdominal and back muscle static strength endurance was observed, which improved in both groups of subjects, however the improved trunk muscle static strength endurance (p=0.029) was fixed in Group II subjects who used spinal stabilization and shock wave therapy cycle. Conclusions. 1. After the cycle of physiotherapy, the pain experienced by the two groups decreased from baseline (from 5 to 6 points) to weak (3 to 2 points) pain. When comparing two groups, a greater reduction in pain was observed in Group II subjects with a spinal stabilization and shock wave therapy cycle. 2. After the cycle of physiotherapy classes, the subjects of both groups increased abdominal and spinal muscular static strength endurance. Greater positive change was fixed in Group II subjects. 3. After the cycle of physiotherapy sessions, the dynamic stability of the subjects improved and the chance of injury was reduced. 4. Comparison between the two groups suggests that the cycle of application of spinal stabilization exercise program and shock wave therapy has a greater positive effect on pain, muscle endurance, dynamic stability and its management.